Factors contributing to poor Biomedical Waste Management among Health Workers in Katabi Military Hospital in Entebbe District. A Cross-sectional Study. - Edward Masagazi; Gordon Nimwesiga (Student's Journal of Health Research Africa, 2022)
Background: